Mass Spectrum of the 3d SU(2) Higgs Model and the Symmetric Electroweak Phase - Philipsen, O; Teper, M; Wittig, H (1996)
We present results for the masses of the low-lying states with quantum numbers $0^{++}$, $2^{++}$ and $1^{--}$ as well as Polyakov line correlations in the Higgs and confinement regions of the 3d SU(2) Higgs model. In the confinement phase we find a dense spectrum of bound states approximately split into two disjoint sectors. One consists of W-balls nearly identical to the glueball spectrum of the pure gauge theory, the other of bound states of scalars.